Establishment of in vitro regeneration system and molecular analysis of early development of somatic callus in Capsicum chinense and Capsicum baccatum - Shu, Huangying; Zhang, Yu; He, Chengyao; Altaf, Muhammad Ahsan; Hao, Yuanyuan; Liao, Daolong; Li, Lin; Li, Caichao; Fu, Huizhen; Cheng, Shanhan; Zhu, Guopeng; Wang, Zhiwei (Frontiers in Plant Science, 2022)
The somatic callus is the main trigger of organ regeneration; however, the mechanisms of how the callus reactivates cell proliferation and promotes cell reprogramming remain elusive in pepper. In the present study, C. baccatum (HNUCB81 and HNUCB226) and C. chinense (HNUCC22 and HNUCC16) were analyzed to reveal callus initiation by in vitro regeneration, histology, and transcriptome. We successfully established an efficient in vitro regeneration system of two cultivars to monitor the callus induction of differential genotypes, and the regenerated plants were obtained. Compared to C. chinense, there was a higher callus induction rate in C. baccatum. The phenotype of C. baccatum changed significantly and formed vascular tissue faster than C. chinense. The KEGG enrichment analysis found that plant hormone transduction and starch and sucrose metabolism pathways were significantly enriched. In addition, we identified that the WOX7 gene was significantly up-regulated in HNUCB81 and HNUCB226 than that in HNUCC22 and HNUCC16, which may be a potential function in callus formation. These results provided a promising strategy to improve the regeneration and transformation of pepper plants.